“Flexible” workplace practices: evidence from a nationally representative survey. - Gittleman, Maury; Horrigan, Michael; Joyce, Mary (Industrial & Labor Relations Review, 1998)
The authors estimate the extent to which establishments have adopted six alternative work organization practices. Findings from the 1993 Survey of Employer Provided Training show that some 42% of all establishments used at least one of these practices, and among establishments with 50 or more employees the figure was nearly 70%. Establishment characteristics that were positively related to the use of the practices were the recent introduction of new technology; large size; manufacturing as the primary activity; incentive-based compensation; the provision of generous benefits; and the use of extensive training. The choice of practices varied greatly among establishments, with no apparent “best practice.” Reprinted by permission of the publisher.